2009
DOI: 10.1021/es9013294
|View full text |Cite
|
Sign up to set email alerts
|

New Approaches to Performance Testing of Improved Cookstoves

Abstract: Monitoring and evaluation of improved cookstove performance is a critical factor in program success; however, consistent evidence indicates water boiling tests and controlled cooking tests are not representative of stove performance during daily cooking activities, and there is no ability to link these tests to kitchen performance tests during normal daily cooking activities. Since emissions from cookstoves contribute heavily to regional estimates of carbonaceous aerosols and other short-lived greenhouse speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 15 publications
2
65
0
Order By: Relevance
“…The relatively high coefficient of variation results from the different influencing parameters (e.g., different amount of dough, different stove setup, skills of cooks) and a very small test sample, but it is comparable to other empirical ICS studies elsewhere [58]. Under laboratory test conditions, where all parameters are standardized, the CCT has a coefficient of variation (CV) between 5% and 10% [59].…”
Section: Efficiency Testingmentioning
confidence: 72%
“…The relatively high coefficient of variation results from the different influencing parameters (e.g., different amount of dough, different stove setup, skills of cooks) and a very small test sample, but it is comparable to other empirical ICS studies elsewhere [58]. Under laboratory test conditions, where all parameters are standardized, the CCT has a coefficient of variation (CV) between 5% and 10% [59].…”
Section: Efficiency Testingmentioning
confidence: 72%
“…As Johnson et al (2010) point out, measurement and verification of emissions reductions in households spread over wide distances are much more complex than, for example, calculating industrial emissions from point-sources such as smoke stacks. Table 3 Barriers for reducing GHG emissions in ICS projects.…”
Section: Measurement and Verificationmentioning
confidence: 99%
“…For CO2 and methane reductions (allowed under Kyoto) Johnson et al (2010) found Mexican Pastari stoves to reduce 3.1 tCO2e home À1 year À1 (95% CI AE 26%), while other stove types, such as Honduran ecofogones have been found to create reductions varying according to stove use, ranging from 0.85 tCO2e to 3.45 tCO2e per year for domestic and commercial use (i.e. cooking tortillas), respectively (Bumpus, 2009).…”
Section: Leakagementioning
confidence: 99%
See 1 more Smart Citation
“…air supply amount and fuel-air mixing conditions) and even experimental methods (e.g. laboratory chamber, simulated stove/open burning, and field measurement) (Shen et al, 2013;Chen et al, 2012;Jetter et al, 2012;Johnson et al, 2010;Jetter & Kariher, 2009).…”
Section: Introductionmentioning
confidence: 99%